PENGARUH KUALITAS LAYANAN DAN KEPERCAYAAN TERHADAP KEPUASAN ORANG TUA SISWA TK BUDI MULIA DUA SEDAYU - Guruh Ghifar Zalzalah; Reni Fitri Yanti; Fikri Farhan (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
This study aims to determine the factors that influence the satisfaction of parents of Budi Mulia Dua Sedayu. Service quality and trust are hypothesized to affect parent satisfaction of Budi Mulia Dua Sedayu Kindergarten students. This study uses quantitative methods. The data collection technique used a questionnaire and interviews. The sampling method in this study used the Random Sampling technique using the slovin formula with a rate of 5% so as to get a sample of 45 respondents. Data analysis of this study using multiple linear regression with the help of SPSS 25 analysis tool. The result of this study indicate that service quality and trust have a positive and significant effect on parent satisfaction of Budi Mulia Dua Sedayu Kindergarten students.